Impact of workflow interruptions on baseline activities of the doctors working in the emergency department - Muhammad Shafiq; Asyia Mobeen; Muhammad Haris Aziz; Muhammad Junaid Mohsin (BMJ Open Quality, 2022)
Background Workflow interruptions are common in the emergency department (ED) of the hospitals for physicians, leading to an increased risk of errors.Purpose This study aims to understand the baseline activities of the ED doctors and how these are affected by workflow interruptions.Methods The study was conducted in two phases to collect the doctor’s perspective (through questionnaire survey) and observer’s perspective (through workflow observation study) about ED doctors’ baseline activities and workflow interruptions. Two different perspectives were obtained to make the insights clearer and more valuable. The point of view of the 223 doctors working in ED of the hospitals was recorded through a questionnaire survey. In the second phase, the observer’s point of view (authors) was obtained through a workflow observation study, and 13 doctors were observed for 160 hours.Results Direct communication with patients (37.1%) and ‘documentation and prescription’ (22.7%) were found to be the most frequent activities. The most common interruptions were visual and auditory distractions, rumination (mind-wandering) and intrusion (by co-workers). Also, the time consumed on indirect patient care (6.6%) was higher than direct patient care (4. 2%). Interruptions increase the chances of errors by making it hard for a doctor to resume a primary task after facing interruptions.Conclusion Interruptions increase the chances of errors and make it difficult for the doctors to resume primary tasks (after facing such incidents).